2016
DOI: 10.1002/hec.3317
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Hearts, Profiteers, or Both: Specialist Physician Fees in an Unregulated Market

Abstract: This study shows that, in an unregulated fee-setting environment, specialist physicians practise price discrimination on the basis of their patients' income status. Our results are consistent with profit maximisation behaviour by specialists. These findings are based on a large population survey that is linked to administrative medical claims records. We find that, for an initial consultation, specialist physicians charge their high-income patients AU$26 more than their low-income patients. While this gap equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 6 publications
(5 reference statements)
0
29
0
Order By: Relevance
“…For patients with private health insurance, the review found mixed results as to whether FT was more or less protected. In Australia, men with prostate cancer experienced FT and higher out-of-pocket expenses when they were privately insured versus public hospital patients [31], which appears to be a product of the unregulated market in which specialists practice price discrimination [36]. However, the opposite was true in the US and other South East Asian countries, where patients without health insurance were more likely to report FT compared to those with health insurance [13,6,37,4,22] but were not always protected from FT.…”
Section: Discussionmentioning
confidence: 97%
“…For patients with private health insurance, the review found mixed results as to whether FT was more or less protected. In Australia, men with prostate cancer experienced FT and higher out-of-pocket expenses when they were privately insured versus public hospital patients [31], which appears to be a product of the unregulated market in which specialists practice price discrimination [36]. However, the opposite was true in the US and other South East Asian countries, where patients without health insurance were more likely to report FT compared to those with health insurance [13,6,37,4,22] but were not always protected from FT.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that doctors in the NT bulk‐bill the large number of patients with limited incomes, but, to compensate for the perceived reduction in income, charge those with the ability to pay much higher fees. Around the country, it is possible that some of the variation in fees is the result of physicians charging different patients different fees, 20 but additional data would be required to determine the magnitude of this practice.…”
Section: Discussionmentioning
confidence: 99%
“…For a number of MBS items, we further analyse whether they are charged differently to different patient groups. Apart from the general inflation and the change in the Medicare base price, doctors and other health providers are free to set prices, and there is evidence that they charge different fees to different patients, especially higher fees for richer patients (Johar, 2012;Johar et al, 2016). It may be the case that providers charge older patients less than younger patients, and this would slow down the growth in expenditure by age, compensating for some of the increase in the intensity of use.…”
Section: Datamentioning
confidence: 99%